2021
DOI: 10.3390/fib9120086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GNPs on the Piezoresistive, Electrical and Mechanical Properties of PHA and PLA Films

Abstract: Sustainability has become the primary focus for researchers lately. Biopolymers such as polyhydroxyalkanoate (PHA) and polylactic acid (PLA) are biocompatible and biodegradable. Introducing piezoresistive response in the films produced by PLA and PHA by adding nanoparticles can be interesting. Hence, a study was performed to evaluate the mechanical, electrical and piezoresistive response of films made from PHA and PLA. The films were produced by solvent casting, and they were reinforced with graphene nanoplate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…An average of five readings was taken and the graph was drawn between voltage and current, where the slope of the graph gives the value of resistance of the sample. After obtaining the resistance R in Ω, electrical resistivity can be calculated by using the equation below [18]. Once the resistivity (ρ) in Ω m was obtained, the inverse of resistivity gave the conductivity (σ) in (S/m).…”
Section: Electrical Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…An average of five readings was taken and the graph was drawn between voltage and current, where the slope of the graph gives the value of resistance of the sample. After obtaining the resistance R in Ω, electrical resistivity can be calculated by using the equation below [18]. Once the resistivity (ρ) in Ω m was obtained, the inverse of resistivity gave the conductivity (σ) in (S/m).…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…Hence, researchers are looking towards GNPs as an alternative to graphene, where they can be produced by ball milling, shear exfoliation, etc. GNPs are attractive as they can be mixed into the polymeric matrix to produce coatings or nanocomposites, and their electrical conductivity is in the order of 6 × 10 3 S/m [18]. Coating of these nanomaterials can be performed via screen printing, which is one of the effective coating techniques alongside pad printing, flexography printing, gravure printing, and roll-to-roll printing.…”
Section: Introductionmentioning
confidence: 99%
“…The blending of flexible PP resin with hard PP resin at various proportions gives rise to enhance the shape memory properties at the same time mechanical properties can also be tailored according to the end-use applications. GNPs are already proven by many researchers that, those are more effective as reinforcement for polymer composites to enhance many properties such as mechanical (Mármol et al , 2021), thermal (Arruda et al , 2022) and electrical (Sanivada et al , 2022). In addition to that, the resin blend is reinforced with GNPs which also adds its part to enhance the mechanical properties along with shape memory behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers reported their research with reinforcements such as graphene nano platelet (GNPs), Fe 3 O 4 , GNPs oxide (GO), multi-walled carbon nanotubes, Nitonol, calcium sulphate whiskers (CSW), Nano silica filler (NSF), SiC, SiO 2 and many more to investigate their effect on shape memory properties. Among all, carbon-based reinforcements (Sanivada et al , 2022) such as GNPs are identified to show their unique properties (Mármol et al , 2021) to achieve improved shape recovery rate and higher shape fixity ratios (Zhang et al , 2021a, 2021b). GNPs are proven by many researchers for their novel abilities in many sectors such as automotive (Moreira et al , 2021), aerospace, defence applications, biomedical such as drug delivery systems, electronics such as smart sensors (Arruda et al , 2022), smart materials such as self-repair, shape changing materials, textiles and nano robots.…”
Section: Introductionmentioning
confidence: 99%